Implementasi Program Anti-Bullying dalam Membangun Budaya Sekolah Inklusif Berbasis Profil Pelajar Pancasila: Studi Kasus di SDN Tonggondoa - Salahuddin, Salahuddin (Bima Journal of Elementary Education, 2025)
This study aims to analyze the effectiveness of the Anti-Bullying Program in fostering an inclusive school culture based on the Pancasila Student Profile (P5) at SDN Tonggondoa, Bima Regency, Indonesia. A qualitative approach with an intrinsic case study design was employed, integrating participatory observation, in-depth interviews, Focus Group Discussions (FGDs), and document analysis of school policies. Data were analyzed using the Miles and Huberman interactive model—comprising data reduction, display, and conclusion drawing—assisted by NVivo 14 Plus to enhance the validity and traceability of findings. The results reveal that the anti-bullying program was implemented systematically, collaboratively, and value-oriented. Strategies such as Salam Pagi (Morning Greeting), Teman Tanpa Bully (Friends Without Bullying), peer mentoring, and restorative mediation effectively reduced bullying incidents by 71%, increased cross-group collaboration by 89%, and enhanced the participation of students with special needs by 133%. Furthermore, the internalization of P5 values—such as moral integrity, cooperation, independence, and critical reasoning—significantly strengthened students’ reflective awareness and social empathy. The synergy between school policies, inclusive culture, and Pancasila values created a sustainable cycle of moral reinforcement in bullying prevention. This study concludes that integrating character education into anti-bullying initiatives is an effective strategy to establish a safe, humanistic, and socially just learning environment. It recommends that national education policies adopt a whole-school approach grounded in Pancasila values as a transformative paradigm for bullying prevention in primary education.